Pengaruh Ekspektasi Pendapatan dan Penggunaan Media Sosial Tiktok terhadap Minat Berwirausaha Mahasiswa STIE IBMT Surabaya - Hilmania, Hilmania; Fadhilllah, Is; Fitriyasari, Anis (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine the effect of income expectations and the use of TikTok social media on entrepreneurial interest of STIE IBMT Surabaya students. In this study the authors used a questionnaire method (questionnaire) to find data directly from students who were taken as samples. The results showed that there is a significant effect of income expectations on student entrepreneurial interest. The results of the t test show that the income expectations variable has a t value of 4.107, which exceeds the t table value of 2.001. This shows that the higher the income expectations, the higher the student entrepreneurial interest. In other words, students who have high income expectations tend to be more interested in engaging in entrepreneurial activities. In addition, this study also found a significant effect of using TikTok social media on students' entrepreneurial interest. The results of the t test show that the variable use of TikTok social media has a calculated t value of 3.312, which also exceeds the t table value of 2.001. This shows that the use of TikTok social media has a positive impact on student entrepreneurship interest. TikTok social media provides a broad means of communication, without distance and time restrictions, and easy access. Therefore, students can utilize this platform to market products and develop creative ideas for entrepreneurship.